Continuous flow nitration of benzaldehyde - Kulkarni, Amol A.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2009)
The nitration of benzaldebyde can be carried out in a safe manner in continuous mode using a microreactor system. Choice of a micromixer was seen to affect the performance of this two-phase reaction significantly The reaction time could he brought down to 2 min by increasing the reaction temperature and thereby taking advantage of higher heat transfer area. The simple T-micromixer is seen to be inefficient for two-phase reactions. Further scope of process intensification is also discussed.